TcellSubC: An Atlas of the Subcellular Proteome of Human T Cells - Joshi, Rubin Narayan; Stadler, Charlotte; Lehmann, Robert; Lehtiö, Janne; Tegnér, Jesper; Schmidt, Angelika; Vesterlund, Mattias (Frontiers in Immunology, 2019)
We have curated an in-depth subcellular proteomic map of primary human CD4+ T cells, divided into cytosolic, nuclear and membrane fractions generated by an optimized fractionation and HiRIEF-LC-MS/MS workflow for limited amounts of primary cells. The subcellular proteome of T cells was mapped under steady state conditions, as well as upon 15 minutes and 1 hour of T cell receptor (TCR) stimulation respectively. We quantified the subcellular distribution of 6572 proteins and identified a subset of 237 potentially translocating proteins, including both well-known examples and novel ones. Microscopic validation confirmed the localization of selected proteins with previously known and unknown localization respectively. We further provide the data in an easy-to-use web platform to facilitate re-use, as the data can be relevant for basic research as well as for clinical exploitation of T cells as therapeutic targets.